2016
DOI: 10.21776/ub.ijeo.2016.001.01.05
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oil of Zingiberaceae Leaf as Antioxidant and Antiglycation

Abstract: Rimpang keluarga Zingiberaceae dilaporkan memiliki aroma khas dan juga aktif sebagai antioksidan, sementara daun keluarga ini memiliki aroma khas yang mirip dengan rimpangnya. Oleh karena itu, penelitian ini bertujuan untuk mengisolasi minyak atsiri daun beberapa spesies dari keluarga Zingiberaceae dan menentukan aktivitas minyak atsiri tersebut sebagai antioksidan dan antiglikasi yang berhubungan dengan anti-penuaan. Daun dari 8 spesies yaitu Alpinia galanga, Boesenbergia pandaratum, Curcuma aeruginosa, Curcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Indeed, some previous studies reported antiglycation activity from plant extracts. Crude extracts from Zingiber zerumbet and essential oil of Zingiber officinale were reported to possess antiglycation activity with IC 50 values of 377.95 and 207.95 µg/ml, respectively [17,25] . In this context, the extract PTR-21 exhibited IC 50 value that was 0.25 to 2-fold higher than other extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some previous studies reported antiglycation activity from plant extracts. Crude extracts from Zingiber zerumbet and essential oil of Zingiber officinale were reported to possess antiglycation activity with IC 50 values of 377.95 and 207.95 µg/ml, respectively [17,25] . In this context, the extract PTR-21 exhibited IC 50 value that was 0.25 to 2-fold higher than other extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Five different Zingiberaceae plants as shown in Table 1 were selected. The essential oils from the leaves of these plants have been reported to show antioxidant, antiglycation, and antibacterial activity against S. mutans as well as demonstrate the ability to degrade the biofilm produced by S. mutans [1,2]. As previously mentioned, the distillation process not only produces essential oils but also residue.…”
Section: Name Of Plants Moisture Content and Ash Content Of Samplesmentioning
confidence: 91%
“…People have used this family of plant to cure various diseases such as fever, skin diseases, digestive disorders, and respiratory disorders. The rhizome is the most used part of this plant, while the leaves had been reported to have high content of essential oils and shown tyrosinase inhibition, antioxidant, antiglycation, and antimicrobial activities [1,2]. Antioxidant and antiglycation are important for health and often associated with antiaging.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activities of fractions were measured based on the radical scavenging activity toward 2,2′-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS), as described previously [ 18 , 19 ]. The antiglycation reactions were carried out by mixing fractions in solution and the glycation substrate based on a previous method [ 20 ].…”
Section: Methodsmentioning
confidence: 99%